(3oZQQ GdHdGZIs - (3gdGd GdUCHjA , gdGd Hf GdeMSf Hf EHQGgje Hf gdGd GdMQGfj, CHh GdMSjf , CHh GdMSf,J (B448 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf Chdi eG oCYedJ ajg GdbQGFM, hYdbJ Hg GdCacGQ GddhGbM, GdaMU YeG ajg Ydh GdeQGJH hSeh GdefGbH s
(3BNQgG (B:s
(3ceG Cf GdehGUdI HGdcJH eY GdGNdGd HGdbdH ZjQ oehGUdI Je GdLRA GdChd ef ZQQ GdHdGZI HMeO Gddg hjJdhg aj GdLRA GdKGfj UOhQ GdcJH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HGdeYgO fSNI CNQis
(3GfXQ aj GdLRA GdChd GdQbe (B615 (3COHs
(3HGdfSNI JbWjYs
(3ajg WGFaI ef QSGFdg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs